Irregular Sound Change due to Frequency in Germanic Languages - Mańczak, Witold (Lingua Posnaniensis, 2010)
Until now, irregular sound change due to frequency has been considered as something sporadic, affecting only the vocabulary, whereas, according to the present writer, irregular sound change due to frequency, which concerns also reductions in morphemes, especially in inflectional ones (which are even more frequently used than words), is the third essential factor of linguistic evolution, in addition to regular sound change and analogical development. There is a synchronic law according to which the linguistic elements which are more often used are smaller than those which are less often used. There is a kind of balance between the size of linguistic elements and their frequency. But if a linguistic element (morpheme, word or group of words) becomes too long in relation to its frequency, it must be shortened.